Specifics procedures for the management of investment risk in the financing of innovative projects - L. A. Bereznikova; S. M. Dli; V. Y. Nesterova (Путеводитель предпринимателя, 2020)
The features of risks accounting and analysis procedures ofinvesting in innovative project were analyzed. The ways of improving the methods of risk management of innovative projects were suggested.